Cylindrical C96 Fullertubes: A Highly Active Metal‐Free O2‐Reduction Electrocatalyst. Issue 21 (23rd March 2022) - Sanad, Mohamed Fathi; Franklin, Hannah M.; Ali, Basant A.; Puente Santiago, Alain R.; Nair, Aruna N.; Chava, Venkata S. N.; Fernandez‐Delgado, Olivia; Allam, Nageh K.; Stevenson, Steven; Sreenivasan, Sreeprasad T.; Echegoyen, Luis
Abstract: A new isolation protocol was recently reported for highly purified metallic Fullertubes D5h ‐C90, D3d ‐C96, and D5d ‐C100, which exhibit unique electronic features. Here, we report the oxygen reduction electrocatalytic behavior of C60, C70 (spheroidal fullerenes), and C90, C96, and C100 (tubular fullerenes) using a combination of experimental and theoretical approaches. C96 (a metal‐free catalyst) displayed remarkable oxygen reduction reaction (ORR) activity, with an onset potential of 0.85 V and a halfway potential of 0.75 V, which are close to the state‐of‐the‐art Pt/C benchmark catalyst values. We achieved an excellent power density of 0.75 W cm −2 using C96 as a modified cathode in a proton‐exchange membrane fuel cell, comparable to other recently reported efficient metal‐free catalysts. Combined band structure (experimentally calculated) and free‐energy (DFT) investigations show that both favorable energy‐level alignment active catalytic sites on the carbon cage are responsible for the superior activity of C96 . Abstract : Oxygen reduction electrocatalytic behavior of C60, C70 (spheroidal fullerenes), and C90, C96, and C100 (tubular fullerenes) is explored using a combination of experimental and theoretical techniques. C96 (a metal‐free catalyst) displayed remarkable oxygen reduction reaction (ORR) activity, with an onset potential of 0.85 V and a halfway potential of 0.75 V, which are close to the state‐of‐the‐art Pt/C benchmark catalyst values.